A naturally occurring null variant of the NMDA type glutamate receptor NR3B subunit is a risk factor of schizophrenia. - Hitomi Matsuno; Kazutaka Ohi; Ryota Hashimoto; Hidenaga Yamamori; Yuka Yasuda; Michiko Fujimoto; Satomi Yano-Umeda; Takeo Saneyoshi; Masatoshi Takeda; Yasunori Hayashi (PLoS ONE, 2015)
Hypofunction of the N-methyl-D-aspartate type glutamate receptor (NMDAR) has been implicated in the pathogenesis of schizophrenia. Here, we investigated the significance of a common human genetic variation of the NMDAR NR3B subunit that inserts 4 bases within the coding region (insCGTT) in the pathogenesis of schizophrenia. The cDNA carrying this polymorphism generates a truncated protein, which is electrophysiologically non-functional in heterologous expression systems. Among 586 schizophrenia patients and 754 healthy controls, insCGTT was significantly overrepresented in patients compared to controls (odds ratio = 1.37, p = 0.035). Among 121 schizophrenia patients and 372 healthy controls, genetic analyses of normal individuals revealed that those carrying insCGTT have a predisposition to schizotypal personality traits (F1,356 = 4.69, p = 0.031). Furthermore, pre-pulse inhibition, a neurobiological trait disturbed in patients with schizophrenia, was significantly impaired in patients carrying insCGTT compared with those with the major allele (F1,116 = 5.72, p = 0.018, F1,238 = 4.46, p = 0.036, respectively). These results indicate that a naturally occurring null variant in NR3B could be a risk factor of schizophrenia.